2013
DOI: 10.2172/1118097
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Flexibility Retrofits for Coal and Gas-Fueled Power Plants: August 2012 - December 2013

Abstract: This report was prepared by General Electric International, Inc. (GE) as an account of work sponsored by NREL. Neither NREL, nor GE, nor any person acting on behalf of either: 1. Makes any warranty or representation, expressed or implied, with respect to the use of any information contained in this report, or that the use of any information, apparatus, method, or process disclosed in the report may not infringe upon privately owned rights 2. Assumes any liabilities with respect to the use of or for damage resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…As noted previously, the mechanisms to change the minimum generation of coal generators could include both changes to operational practices as well as physical modifications. Further explanation of retrofits to individual generators is provided in Venkataraman et al (2013), which found that benefits to the system are comparable to the costs of implementation. Cochran et al (2013) addresses some of these physical modifications and also summarizes many of the implications and challenges of the operational changes that would be required to run coal plants at lower output.…”
Section: Increased Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, the mechanisms to change the minimum generation of coal generators could include both changes to operational practices as well as physical modifications. Further explanation of retrofits to individual generators is provided in Venkataraman et al (2013), which found that benefits to the system are comparable to the costs of implementation. Cochran et al (2013) addresses some of these physical modifications and also summarizes many of the implications and challenges of the operational changes that would be required to run coal plants at lower output.…”
Section: Increased Flexibilitymentioning
confidence: 99%
“…It uses a subset of the Western Interconnection electric power system to quantify the impact of increased generator flexibility on overall production costs. Flexibility of this test system has been previously analyzed by Venkataraman et al (2013), which included a costbenefit analysis of certain retrofits available for combined-cycle and coal generation plants. They found that increased flexibility of a few plants decreased the costs of operating the system and were commensurate with the costs of installing the necessary upgrades.…”
Section: 20 1 Introductionmentioning
confidence: 99%
“…In the past decade, energy utilities have been evaluating numerous refurbishment options or new operation practices to reduce the costs of the flexible operation of their thermal units and increase their capability to meet peak demand (suggested best practices have been reported in industrial literature [36,37]). Therefore, the power plant configuration and the corresponding cycling capability are variables of the energy system configuration-they can be optimised together with the supply mix as functions of costs and demands, in order to assess least-cost options to increase reliability of supply in scenarios with significantly increasing penetration of intermittent renewables.…”
Section: Refurbishment Optionmentioning
confidence: 99%
“…Flexible generation refers to increasing the ramp rate and range of conventional generators to respond better to the net load shape created by additional PV. It also refers to increasing the ability to start and stop generators more frequently (Palchak and Denholm 2014;Venkataraman et al 2013).…”
Section: Flexible Generationmentioning
confidence: 99%
“…Technical changes can also provide more flexibility from individual generators. New gas-fired generation typically can provide significant ramp rates and multiple operating reserves (Venkataraman et al 2013). Certain new gas-fired combustion turbines and reciprocating engines are capable of very short start times, and these units could even provide some fraction of traditional synchronized (spinning) reserves without being online (Wärtsilä and Energy Exemplar 2014).…”
Section: Flexible Generationmentioning
confidence: 99%